Pengujian konsumsi daya baterai litium-ion pada sepeda motor listrik dengan variasi kemiringan lintasan - Zain, A.T.; Suranto, D.D.; Irawan, A.; Karimah, C.N. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2023)
The development of electric vehicles in Indonesia, especially the BEV (Battery Electric Vehicle) type, has received serious attention and support from the government. This is evidenced by the issuance of Presidential Regulation Number 55 of 2019 concerning the acceleration of the Battery-Based Electric Motor Vehicle Program for Road Transportation. Electric vehicles designed and developed in this study use an on-wheel BLDC type electric motor, Li-Ion batteries and are equipped with a watt hour meter to monitor battery consumption. The results of testing the accuracy and precision of the watt hour meter show a good value. This is evidenced by the difference in the measurement value of the watt hour meter against the Avometer and the difference between each repetition of the data 5 times which is below 1 Volt and 1 Ampere. Other test results show that the track with a large slope will also experience a large voltage drop, namely 0.8 V at a slope of 100 and the maximum current flowing is 8.35 A. Meanwhile, when the slope of the track is 70 and 60, the battery voltage decreases and the current flowing respectively are 0.5 V and 8.12 A; as well as 0.2 V and 7.84 A.